Nasolabial Dimensions of the Facial Profile at 20 to 37 Weeks' Gestation on 2‐ and 3‐Dimensional Sonography in Normal Korean Fetuses. (1st April 2013) - Ko, Hyun Sun; Lee, U-Young; Choi, Sae Kyung; Park, Yong-Gyu; Park, In Yang; Shin, Jong Chul
Abstract : Objectives: The purpose of this study was to evaluate normal nasolabial dimensions using the images of facial profiles in normal Korean fetuses. Methods: We conducted a cross‐sectional study of 355 normal fetuses at 14 to 39 weeks' gestation. After the exclusion of inadequate images and inadequate numbers of fetuses at 14 to 19 and 37 to 39 weeks' gestation, the sonographic facial profiles from 222 fetuses at 20 to 37 weeks' gestation were evaluated. Five parameters, nose length, nose protrusion, pronasal‐subnasal distance, distance between the upper philtrum and mouth, and distance between the tip of the nose and mouth, were measured and are presented according to gestational age. Data were analyzed by intraclass correlation coefficients and regression analysis. Results: There were significant linear correlations between gestational age and nose length ( R = 0.390; P < .001), pronasal‐subnasal distance ( R = 0.415; P < .001), and distance between the upper philtrum and mouth ( R = 0.315; P < .001). There were significant quadratic relationships between gestational age and nose protrusion ( R 2 = 0.213; P < .001) and distance between the tip of the nose and mouth ( R 2 = 0.173; P < .001). Conclusions: We provide preliminary normative nasolabial dimensions of facial profiles at 20 to 37 weeks' gestation in normal Korean fetuses. These data may be of help not only in the understanding of normal nasolabial growth in utero but also in the diagnosis of abnormal facial dimensions.